Change in injection angle as alternative for diesel engine fueled with biodiesel blends - Paiva, Paulo Henrique; Gurgacz, Flavio; Gralick, Jonas; Bassegio, Doglas; Souza, Samuel Nelson Melegari de; Secco, Deonir (Acta Scientiarum. Technology, 2022)
Biodiesel properties have a significant impact on engine performance. The disadvantages of biodiesel include poor atomization. To overcome this problem, engine parameters such as the injection angle can be changed. The objective of this study was to evaluate the effect of changes in the injection angle of an injector pump on the performance of a diesel engine fueled with various biodiesel blends. The experimental design involved testing three injection angles: 26°, 28°, and 30°; and four biodiesel blends: B0, B8, B15, and B20. The effects of variations in these factors were evaluated in terms of the maximum power, rotation at maximum power, torque at maximum power, maximum torque, rotation at maximum torque, specific fuel consumption, engine elasticity index, torque reserve, and rotation reserve. The engine fueled with the biodiesel blends showed a lower specific consumption without losing power or torque, when the crank angle of the injector pump was changed from its original configuration of 26° to 28°.